1996
DOI: 10.1111/j.1365-2133.1996.tb01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients with psoriasis have elevated levels of serum eosinophil cationic protein and increased numbers of EG2 positive eosinophils in the duodenal stroma

Abstract: The occurrence of EG2-positive (EG2+) eosinophils and IgE in biopsy specimens of duodenal mucosa and skin from 39 psoriasis patients was studied, with emphasis on the relation to serum eosinophil cationic protein (ECP), serum IgE and the presence or absence of serum IgA and IgG antigliadin antibodies. Psoriasis patients had significantly elevated serum levels of ECP even after exclusion of five of 37 sera which were Phadiatop positive. The elevated serum ECP was not associated with the presence of IgA or IgG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Interestingly, eosinophils were increased in psoriasis patients compared with controls. Although it may be due to selection bias, some reports had addressed elevation of eosinophil cationic protein in the serum of psoriasis patients and pruritus in psoriasis and found it to be associated with eosinophil activation . Hb level was significantly decreased in PsA patients compared with both psoriasis patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, eosinophils were increased in psoriasis patients compared with controls. Although it may be due to selection bias, some reports had addressed elevation of eosinophil cationic protein in the serum of psoriasis patients and pruritus in psoriasis and found it to be associated with eosinophil activation . Hb level was significantly decreased in PsA patients compared with both psoriasis patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, psoriatic patients present with elevated levels of eosinophil cationic protein (ECP), both in the serum and affected skin [14,43]. Elevated serum ECP is linked to psoriasis, irrespective of disease severity; however, values were observed in patients presenting with moderate and severe psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum ECP is linked to psoriasis, irrespective of disease severity; however, values were observed in patients presenting with moderate and severe psoriasis. Moreover, Michaelsson et al [43] found that patients with psoriasis presented with low EG2 positive (EG2+) activated eosinophils in the skin and higher levels of EG2+ activated eosinophils in the duodenum compared to those with irritable bowel syndrome, even in association with negative gliadin antibodies. These findings indicate that it is highly unlikely in such cases for elevated serum ECP to be due to eosinophil activation in the skin and thus suggest that elevated EG2+ activated eosinophils in the duodenum may properly reflect the inflammatory activity of psoriatic skin.…”
Section: Discussionmentioning
confidence: 99%